Thermally Controlled Shape-Memory Investigations of Nanocomposites Based on Oligo(ω-pentadecalactone) and Magnetic Nanoparticles Acting as Crosslinks. Issue 1718 (2015) - Razzaq, M. Yasar; Behl, M.; Lendlein, A.
ABSTRACT: Covalent integration of inorganic nanoparticles into polymer matrices leads to a homogenization of their distribution and enhances the structural properties. Here, we report on a thermally-controlled reversible shape-memory effect (R-SME) of magnetic nanocomposites under stress-controlled conditions. The magnetic nanocomposites consisted of an oligo( ω -pentadecalactone) (OPDL) matrix with covalently integrated or physically added magnetic nanoparticles (MNP). The R-SME of these materials was based on crystallization-induced elongation (CIE) and melting-induced contraction (MIC) under a constant stress in thermomechanical experiments. Furthermore, the adjustability of the recovery stress in magnetic nanocomposites as a function of MNP content was investigated. A slight increase in the recovery stress from 0.9 MPa for pure OPDL network to 1.2 MPa for H-NC containing 9 wt% of covalently integrated MNP was observed.